Optimization of Formulation and Physical Evaluation of Peel-Off Gel Face Mask from Clove Leaf Essential Oil (Syzygium aromaticum L.) - Miftahul Jannah, Nadia; Prasetyo, Yogi (Journal of Food and Pharmaceutical Sciences, 2025)
Acne is an inflammatory infection triggered by Propionibacterium acnes bacteria. Clove leaf essential oil (Syzygium aromaticum L.) has attracted attention as a potential active ingredient in skincare products, such as peel-off gel face masks, due to its anti-inflammatory properties. This study aims to develop a natural, effective, and safe skincare product for treating acne using clove leaf essential oil as the active ingredient. The active ingredient was 2% essential oil, with formulation optimization of PVA (1–2.5%) and propylene glycol (5–6.5%). The physical evaluation of the formulations included organoleptic properties, homogeneity, pH, spreadability, viscosity, and drying time. The optimum formulation of the peel-off gel face mask containing clove leaf essential oil was achieved with a PVA concentration of 1.163% and propylene glycol at 6.333%, with a desirability value of 1.000. The physical evaluation results of the optimum formula showed a pH value of 5.90, a spreadability of 6.60 cm, a drying time of 26.08 minutes, and a viscosity of 30,682.50 cps.